2004
DOI: 10.1080/15216540500037406
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia/Ischemia and the Regulation of Neuroglobin and Cytoglobin Expression

Abstract: SummaryIn analogy to hemoglobin (Hb) and myoglobin (Mb), neuroglobin (Ngb) and cytoglobin (Cygb) are supposed to be involved in oxygen (O 2 ) storage and delivery. The Cygb gene harbours both conserved HREs and mRNA stabilization sites, strongly suggestive of an oxygen-dependent regulation. We examined the relative transcriptional changes of Ngb and Cygb in a situation of chronic hypoxia using real-time quantitative PCR. We could conclude that Cygb is a hypoxia-induced gene, which is transcriptionally upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 28 publications
3
58
0
1
Order By: Relevance
“…However, the absolute levels of expression of CYGB were very low in three of the cell lines, which had promoter methylation 40.95. These data imply that there may be alternate control mechanisms for the activation of this gene and may be explained by observations of hypoxia responsive mRNA stabilisation sites in the gene (Fordel et al, 2004a). These trends largely replicate in vitro our ex vivo cross-sectional tissue data and lend further support to the role of tissue hypoxia in the regulation of CYGB.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, the absolute levels of expression of CYGB were very low in three of the cell lines, which had promoter methylation 40.95. These data imply that there may be alternate control mechanisms for the activation of this gene and may be explained by observations of hypoxia responsive mRNA stabilisation sites in the gene (Fordel et al, 2004a). These trends largely replicate in vitro our ex vivo cross-sectional tissue data and lend further support to the role of tissue hypoxia in the regulation of CYGB.…”
Section: Discussionsupporting
confidence: 77%
“…Subsequent studies on hippocampal cell lines confirmed that hypoxia upregulates CYGB mRNA expression in a 'dose-dependent' manner (Fordel et al, 2004a, b). Further work on HIF1A ( þ /1) knockout mice confirmed that this effect is mediated by the HIF1A pathway and also that the CYGB gene contains hypoxia responsive elements and mRNA stabilisation sites (Fordel et al, 2004a). Hypoxia is a known endogenous marker of poor prognosis in HNSCC.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Overexpression of NGB did not affect the basal level of IOP, and injection of microbeads in Ngb-Tg mice induced a kinetic of IOP elevation similar to that of the wild-type littermates ( Figure 1D). However, elevated IOP resulted in an increase in NGB expression in the retina, including the GCL, INL, and OPL, in wild-type mice ( Figure 1B), Neuroglobin 6 relative to expression in PBS-injected eyes. Immunolabeling of NGB in Ngb-Tg mice also confirmed high levels of NGB expression in the GCL and other retinal layers ( Figure 1C).…”
Section: Ngb Expression Profile In Response To Iop Elevationmentioning
confidence: 99%
“…Robust in vivo induction of Mb genes by chronic hypoxia, regardless of the training status of the animals, was previously observed in zebrafish gills (8) and in striated muscle of mice (9). The master regulator of cellular O 2 homeostasis, the hypoxia-inducible transcription factor 1 (HIF-1), has been implicated in the mouse for this transcriptional activation (9).…”
mentioning
confidence: 99%